Effusion Cytology of Dysgerminoma: A Case Report with Review of Literature - Balakrishnan, Meera; George, Smiley Annie; Mallik, Anupama Arora; Mallik, Mrinmay Kumar (Annals of Pathology and Laboratory Medicine, 2023)
Ovarian dysgerminoma is a rare malignant ovarian germ cell tumor (MOGT) with its peak incidence in women younger than 20 years. Peritoneal and pleural dissemination of ovarian tumors is a major prognostic parameter in ovarian malignancies. Effusion cytology of germ cell tumors are not frequently reported in the literature. We report a case of a MOGT in a 15 year old female who presented with severe painful abdominal distention and respiratory distress. Ascitic and pleural fluid cytology were positive for malignant cells which on immunocytochemistry supported the diagnosis of metastatic dysgerminoma. The histopathology of the ovarian mass was confirmed to be dysgerminoma FIGO stage IVA. This case report highlights the salient cytomorphologic features of metastatic dysgerminoma in ascitic and pleural fluid discussing the differential diagnoses.